Bhuvamaaneetaa bhagavadbhaashaa: a narrative on the revival of hebrew) - Vishwas H.R. (Sanskrit bharati, Banglore, 2004)
Sanskrit
SANSKRIT
Keywords: Bhuvamaaneetaa bhagavadbhaashaa: a narrative on the revival of hebrew); Sanskrit; Sanskrit